Tunable magnetic coupling in Mn-doped monolayer MoS2 under lattice strain. (2nd May 2018) - Miao, Yaping; Huang, Yuhong; Bao, Hongwei; Xu, Kewei; Ma, Fei; Chu, Paul K
Abstract: First-principles calculations are conducted to study the electronic and magnetic states of Mn-doped monolayer MoS2 under lattice strain. Mn-doped MoS2 exhibits half-metallic and ferromagnetic (FM) characteristics in which the majority spin channel exhibits metallic features but there is a bandgap in the minority spin channel. The FM state and the total magnetic moment of 1 µ B are always maintained for the larger supercells of monolayer MoS2 with only one doped Mn, no matter under tensile or compressive strain. Furthermore, the FM state will be enhanced by the tensile strain if two Mo atoms are substituted by Mn atoms in the monolayer MoS2 . The magnetic moment increases up to 0.50 µ B per unit cell at a tensile strain of 7%. However, the Mn-doped MoS2 changes to metallic and antiferromagnetic under compressive strain. The spin polarization of Mn 3 d orbitals disappears gradually with increasing compressive strain, and the superexchange interaction between Mn atoms increases gradually. The results suggest that the electronic and magnetic properties of Mn-doped monolayer MoS2 can be effectively modulated by strain engineering providing insight into application to electronic and spintronic devices.